Evaluation of the safety and nutritional equivalency of maize grain with genetically modified event DP-Ø23211-2. Issue 1 (2nd January 2021) - Smith, Brenda L.; Zimmermann, Cindi S.; Carlson, Anne B.; Mathesius, Carey A.; Mukerji, Pushkor; McNaughton, James L.; Walker, Carl A.; Roper, Jason M.
ABSTRACT: Feeding studies were conducted with rats and broiler chickens to assess the safety and nutrition of maize grain containing event DP-Ø23211-2 (DP23211), a newly developed trait-pyramid product for corn rootworm management. Diets containing 50% ground maize grain from DP23211, non-transgenic control, or non-transgenic reference hybrids (P0928, P0993, and P1105) were fed to Crl:CD®(SD) rats for 90 days. Ross 708 broilers were fed phase diets containing up to 67% maize grain from each source for 42 days. Body weight, gain, and feed conversion were determined for comparisons between animals fed DP23211 and control diets in each study. Additional measures included clinical and neurobehavioral evaluations, ophthalmology, clinical pathology, organ weights, and gross and microscopic pathology for rats, and carcass parts and select organ yields for broilers. Reference groups were included to determine if any observed significant differences between DP23211 and control groups were likely due to natural variation. No diet-related effects on mortality or evaluation measures were observed between animal fed diets produced with DP23211 maize grain and animal fed diets produced with control maize grain. These studies show that maize grain containing event DP-Ø23211-2 is as safe and nutritious as non-transgenic maize grains when fed in nutritionally adequate diets. The results are consistent with previously published studies, providing further demonstration of the absence of hazards from edible-fraction consumption of genetically modified plants.